Modern aspects of accomplishment of currency transactions by credit organizations - L. V. Alekseeva (Russian Journal of Economics and Law, 2008)
The article opens the basic aspects of service by banks of foreign economic activities of legal entities. Foreign economic activities of the enterprises work by means of international payments system. Banks, being intermediaries in international payments, organize money movement of participants of foreign trade activities. Hence, developing the letter of credit method of payments is necessary with the purpose of regulation of non-payments risks and sharing of banks in syndicate underwriters for maintenance by additional money resources of the enterprises. It promotes timeliness and completeness of receipt of export proceeds on accounts of participants of foreign economic activities, and also profitability of their activity.